The Influence of Perceived Organizational Support and Job Satisfaction towards Employee Performance at PT Samudera Perdana Selaras - Arief - Wikantono; Dody - Setyadi; Kurniani - Kurniani (Politeknik Negeri Semarang, 2021)
The aim of this study is to analyze the influence of perceived organizational support and job satisfaction on employee performance at PT Samudera Perdana Selaras. The study uses quantitative approach, samples that used in this study is 36 employees. Data collection method is questionnaire. Data analyze technique is multiple linear regression analysis equipped with a classic assumption test, t test, f test, and coefficient of determination with software SPSS 26. The regression equation is Y = 16.035 + 0.171 X1 + 0.636 X2. Coefficient of determination (R²) is 0.579. The result of this research showed that perceived organizational support (X1) has no partial influence on employee performance (Y), job satisfaction (X2) has partial positive significant influence on employee performance (Y). The results also show that the perceived organizational support and job satisfaction simultaneously and significantly has a positive effect on employee performance.